Martin Luther King, Jr. civil rights leader [videorecording] - Baber, Jerry; Fabian, Rhonda; Schlessinger, Andrew (Bala Cynwyd, Pa. Schlessinger Video Productions, 1992)
A short biography of Martin Luther King, Jr. Contains interviews with leading authorities on King's life.
Adapted from the book Martin Luther King, Jr. : civil rights leader of Robert Jakaubek published by Chelsea House.
VHS.
Narrator, Michael Logan.
Keywords: King, Martin Luther -- Jr. -- 1929-1968.; Afro-Americans -- Civil rights